Development of a reliable GC-MS method for fatty acid profiling using direct transesterification of minimal quantities of microscopic orchid seeds. Issue 1 (22nd December 2015) - Colville, Louise; Marks, Tim R.; Pritchard, Hugh W.; Custódio, Ceci C.; Machado-Neto, Nelson B.
Abstract: Orchid seeds are among the smallest seeds in nature and they are naturally rich in fatty acids. However, the fatty acid composition of orchid seeds has not been investigated because the sample masses utilized for widely used methods for fatty acid profiling would generally require prohibitively large numbers (i.e. 10, 000s) of seeds. The present work aimed to develop a method for fatty acid analysis using gas chromatography–mass spectrometry on small quantities (mg) of seeds. The method was developed using the seeds of two species, Dactylorhiza fuchsii, a temperate terrestrial, and Grammatophyllum speciosum, a tropical epiphyte. A range of sample masses was tested to determine the minimum mass required to achieve reliable fatty acid composition data. A direct transesterification method was used, which did not require extraction of fatty acids from seeds prior to analysis, and the effects of seed processing (crushed versus intact seeds) and incubation time in toluene on fatty acid yield were tested. Stable fatty acid profiles were obtained using as little as 10 mg of seeds. Neither crushing the seeds nor extending the toluene incubation step had much effect on the fatty acid yield. The simple direct transesterification method presented will enable the fatty acid composition of orchid seeds, and possibly other small seeds, to be determined reliably for studies into seed development, storage and germination.